2022
DOI: 10.21037/tcr-22-992
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a combined ferroptosis and immune prognostic signature for lung adenocarcinoma

Abstract: Background: Studies have shown that the regulation of ferroptosis could be a new approach to cancer treatment and abnormal ferroptosis is closely associated with a dysregulated immune response. However, a combined signature with ferroptosis-related genes (FRGs) and immune-related genes (IRGs) is necessary to be constructed for predicting prognoses and guiding individualized precision therapy of lung adenocarcinoma (LUAD) patients.Methods: In this study, based on the Cancer Genome Atlas (TCGA) cohort, prognosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Some studies related to prognostic gene signature, have been reported in LC (19)(20)(21). Li et al constructed a combined ferroptosis and immune prognostic signature for lung adenocarcinoma (10). Gong et al developed a novel signature based on autophagy-related lncRNA in lung adenocarcinoma (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies related to prognostic gene signature, have been reported in LC (19)(20)(21). Li et al constructed a combined ferroptosis and immune prognostic signature for lung adenocarcinoma (10). Gong et al developed a novel signature based on autophagy-related lncRNA in lung adenocarcinoma (11).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the prognostic gene signatures of autophagy, ferroptosis and immune were established in lung adenocarcinoma (10)(11)(12), however, the role of macrophagesrelated genes in the prognosis of LC remains unclear. Considering M1 macrophages are considered antitumor factors, we focused on the essential role of M1 macrophages in LC to construct an M1-related gene signature for the LC cohort, demonstrating that it has independent prognostic value, as well as exploring the clinical utility for LC patients.…”
Section: Introductionmentioning
confidence: 99%